A New, Phenotypically Distinct Subpopulation of Regulatory Killer T ex-Th17 Cells Expressing CD4lowCD25hiCD49hiFoxp3hiRORlowIL-17low (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: regulatory killer t ex-th17 cells; etregs; CD4lowCD25hiCD49hifoxp3hiRORlowIL-17low cells